2009
DOI: 10.1007/s11244-009-9187-3
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Manganese Oxide Catalysts for the Total Oxidation of Ethyl Acetate

Abstract: Manganese oxide catalysts were synthesized by direct reaction between manganese acetate and permanganate ions, under acidic and reflux conditions. Parameters such as pH (2.0-4.5) and template cation (Na ? , K ? and Cs ? ) were studied. A pure cryptomelane-type manganese oxide was synthesized under specific conditions, and it was found that the template cation plays an important role on the formation of this kind of structure. Cryptomelane was found to be a very active oxidation catalyst, converting ethyl aceta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(52 citation statements)
references
References 35 publications
4
47
0
1
Order By: Relevance
“…The values obtained are within the values reported in the literature (87-119 m 2 /g) for mesoporous MnO x materials prepared using mesoporous silica KIT-6 as a hard template [6]. Lower values (ranging from 0.3 to 82 m 2 /g) have been reported using traditional methods [10,16,18,20,24,25,27,[29][30][31][32]. Higher values ranging from 144 to 316 m 2 /g are less frequent [19,24,27,31].…”
Section: N 2 Adsorptionsupporting
confidence: 86%
See 2 more Smart Citations
“…The values obtained are within the values reported in the literature (87-119 m 2 /g) for mesoporous MnO x materials prepared using mesoporous silica KIT-6 as a hard template [6]. Lower values (ranging from 0.3 to 82 m 2 /g) have been reported using traditional methods [10,16,18,20,24,25,27,[29][30][31][32]. Higher values ranging from 144 to 316 m 2 /g are less frequent [19,24,27,31].…”
Section: N 2 Adsorptionsupporting
confidence: 86%
“…Figure 2 shows the XPS spectra of selected samples and Table 2 shows the binding energies of the doublet separation of Mn 3 s, which Galakhov et al [33] proposed to determine the average oxidation state (AOS) of manganese. The same authors show that the energy difference (DEs) between the main peak and its satellite decreases monotonically with the increase of the AOS of the manganese [32]. As can be seen in Table 2 the materials have an AOS between 2.45 and 3.30, which is in agreement with the mixture of manganese phases in each sample.…”
Section: Xrdsupporting
confidence: 59%
See 1 more Smart Citation
“…Conversely, a decrease in activity happened from 250°C to 280°C. The same result was obtained by Santos et al (2009) where they observed a strong adsorption of toluene to cause a decrease in the catalytic activity. This was explained in their other study (Santos et al 2012) where they found Although the lack of fit for both toluene and benzene decomposition were both significant, it was caused by the computed values which were greater than 100% while the maximum experimental value was only 100%.…”
Section: Physical Characteristic Propertiessupporting
confidence: 82%
“…El óxido mixto ACMn presentó una señal más intensa en la reducción de Mn 3 O 4 → MnO, lo que puede asociarse a un mejor desempeño catalítico en reacciones de oxidación, ya que, como se ha establecido, los óxidos de manganeso con átomos de Mn en diferentes estados de oxidación, como es el caso de la hausmanita Mn 3 O 4 , propician un ambiente de movilidad electrónica óptimo para efectuar una reacción de óxido-reducción sobre su superficie (Santos, et al, 2009). …”
Section: Caracterización De Los óXidos Mixtosunclassified